Women's studies : the basics - Smith, Bonnie G., 1940- (Basics (Routledge (Firm)), 2013)
Women's Studies: The Basics is an accessible introduction into the ever expanding and increasingly relevant field of studies focused on women. Tracing the history of the discipline from its origins, this text sets out the main agendas of women's studies and feminism, exploring the global development of the subject over time, and highlighting its relevance in the contemporary world. Reflecting the diversity of the field, core themes include: the interdisciplinary nature of women's studies core feminist theories and the feminist agenda issues of intersectionality: women, race, class and gender women, sexuality and the body global perspectives on the study of women the relationship between women's studies and gender studies. Providing a firm foundation for all those new to the subject, this book is valuable reading for undergraduates and postgraduates majoring in women's studies and gender studies, and all those in related disciplines seeking a helpful overview for women-centred, subject specific courses.